PRINSIP CABOTAGE DALAM INDUSTRI PENERBANGAN INDONESIA DI ERA ASIAN SINGLE AVIATION MARKET 2015 - Adi Kusuma Ningrum (Arena Hukum, 2012)
AbstractASEAN Single Aviation Market 2015, is a policy that has been agreed by all ASEAN member countries.This agreement called ASEAN Multilateral Agreement on Air Services (ASEAN MAAS) and was signedon May 20, 2009 in Manila, Philippines. Despite the many advantages and potential benefits from theopen sky policy, the government should be aware of the threat in the ASEAN aviation market, such as themarket share of domestic flights among domestic and foreign airline in this region. Futhermore, controlforeign investment in the field of air transport in Indonesia is weak, thus opening the possibility ofsmuggling investment law through the establishment of an Indonesian legal entity. Cabotage principleobjective is maintaining and protecting the political and economic interests of the country. Applicationof the principle of cabotage could be operationally flexible, as long as the country's strategic interestsis maintained and protected. Aviation services in Indonesia is currently considered to have violated theprinciple of cabotage.Key words: cabotage, aviation, market, ASEANAbstrakPasar tunggal penerbangan ASEAN (ASEAN Single Aviation Market) pada tahun 2015, merupakan kebijakanyang telah disepakati oleh seluruh negara anggota ASEAN yang tertuang dalam ASEAN MultilateralAgreement on Air Services (ASEAN MAAS) dan telah ditandatangani pada tanggal 20 Mei 2009di Manila, Filipina. Dalam menghadapi ASEAN Single Aviation Market 2015, selain memperhatikanpotensi keuntungan yang dapat diperoleh dari kebijakan open sky tersebut, pemerintah harus mewaspadaipeluang ancaman perebutan pangsa pasar penerbangan di wilayah ASEAN juga pangsa pasar penerbangandomestik. alah satu faktor yang dapat mengancam Indonesia adalah lemahnya pengawasan(direct or indirect) investment bidang angkutan udara, sehingga kemungkinan terjadi penyelundupanhukum investasi, yang akhirnya pasar nasional dikuasai asing melalui badan hukum Indonesia yangdibentuknya (cabotage terselubung). Prinsip cabotage diterapkan secara umum di seluruh dunia dengantujuan menjaga dan melindungi kepentingan politik dan ekonomi negara yang bersangkutan. Penerapanprinsip cabotage secara operasional bisa bersifat fleksibel, selama kepentingan strategis negara tersebuttetap terjaga dan terlindungi. Pelayanan penerbangan di Indonesia saat ini dianggap sudah melanggarprinsip cabotage.Kata kunci: cabotage, penerbangan, pasar, ASEAN